Peningkatan Kemampuan Pemahaman Konsep Matematis Siswa Melalui Model PBL Dengan Pendekatan TaRL Pada Materi Bentuk Akar - Apriliyani, Rozita; Rhomdani, Rochmad Wahid; Ariyanto, Septian Tri (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2025)
Based on the results of observations that have been carried out at SMP Negeri Kalisat, it was found that students' mathematical concept understanding abilities are still low. The purpose of this study was to analyze the improvement of students' mathematical concept understanding through the application of the PBL model with the TaRL approach in the material of root forms in class X.1 of SMA Negeri Kalisat. The type of research used was classroom action research which was carried out in two learning cycles. The subjects of this study were students of class X.1 of SMA Negeri Kalisat in the 2024/2024 academic year. The data collection instruments used included observation sheets for teacher activities, student activities, and tests of students' mathematical concept understanding abilities. The results of this study indicate that there was an increase in students' mathematical concept understanding abilities in the material of root forms in class X.1 of SMA Negeri Kalisat with an increase in the average ability of students' mathematical concept understanding abilities from 57.17 and a percentage of completion of 28.6% in cycle I increasing to 85.82 and a percentage of completion of 80% in cycle II.